Keratoconus Features on Corneal Higher-Order Aberration Ablation Maps: Proof-of-Concept of a New Diagnostic Modality - Wallerstein A (Dove Medical Press, 2021)
Avi Wallerstein,1,2 Mathieu Gauvin,1,2 Michael Mimouni,3 Louis Racine,4 Ali Salimi,1,2 Mark Cohen2,5 1Department of Ophthalmology and Visual Sciences, McGill University, Montreal, QC, Canada; 2LASIK MD, Montreal, QC, Canada; 3Department of Ophthalmology and Vision Sciences, University of Toronto, Toronto, ON, Canada; 4Department of Ophthalmology, University of Montreal, Montreal, QC, Canada; 5Department of Surgery, University of Sherbrooke, Sherbrooke, QC, CanadaCorrespondence: Avi Wallerstein 1250 Rene-Levesque Blvd W, MD Level, Montreal, QC, H3B 4W8, CanadaTel +1 514-908-9888, Ext. 2273Email awallerstein@lasikmd.comPurpose: To assess the potential application of corneal higher-order aberration (HOA) excimer ablation map imaging in identifying reproducible keratoconus (KC) features and to explore if newly derived map metrics correlate to Pentacam KC indices.Methods: Case series of 12 eyes with KC ≥ grade 2. Topolyzer Vario corneal imaging with its resultant HOA ablation map islands were analyzed for their centroid, distance from center, angular position, orientation, sphericity, diameter, area, and maximal ablation depth. Correlations to Pentacam indices were studied.Results: All eyes showed recurrent features with an arrangement of two elliptical paracentral ablation islands, one deep inferotemporal and one shallow superonasal, in direct mirror-like opposition to each other. These were always accompanied by superior peripheral ablation crescents. The two paracentral islands had highly reproducible distance from center (1.2 ± 0.1 mm and 1.3 ± 0. 2 mm) and angular positions (246.8 ± 15.9° and 76.7 ± 7.7°), with greater variation in ablation depth (68.3 ± 33.2 μm and 17.6 ± 12.1 μm). Distance from center of the peripheral superior crescents was highly reproducible (3.3 ± 0.1 mm), with a larger range of depth (74.5 ± 37.2 μm). The deep paracentral inferotemporal island “hot spot” was coincident with the topographical apical cone. Strong correlations were found between the depth of the inferotemporal island and Pentacam indices of posterior radius curvature (PRC: R = − 0.74) and Belin/Ambrosio enhanced ectasia total deviation (BAD-D: R = 0.71).Conclusion: The corneal HOA ablation map revealed a recurring, distinct, easily recognizable pattern in KC eyes. There was a strong correlation between the depth of novel HOA ablation map metrics and validated Pentacam KC indices. Novel information can be extracted from the corneal HOA ablation map giving it the potential to be a new modality to diagnose and grade KC.Keywords: topography, Contoura, keratoconus, ectasia, diagnosis, higher-order aberration